Optimalization of SPSS Mastery as a Support for Students’ Thesis - Mellyzar; Isna Rezkia Lukman; Nanda Novita; Syafrizal; Fajrul Wahdi Ginting; Muliani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this activity is to introduce SPSS software to students in the form of the benefits of SPSS software, how to install SPSS software and ways to operate SPSS software from prerequisite testing to hypothesis testing in educational research. The stages of this activity consist of the preparation stage, the implementation stage, and the evaluation stage. The results achieved in the in outline students are able to understand the concepts, theories, and functions of SPSS, and students were able to perform data processing using the SPSS application. The conclusion from the results of this service is that students can understand concepts related to SPSS and how to do data analysis. Student response to activities is good. With a percentage level of understanding of the material at 72.5%, motivation at 77.5%, time allocation at 70.5% with good criteria, and an assessment of the speaker's performance at 86% with very good criteria.